Appreciating vulgarity in raw Zimdancehall music as expression of truth - Parwaringira, Blessed; Mpofu, Phillip (Routledge, 2022)
While there are refined creations, vulgarised Zimdancehall has been a subject of academic, political and cultural concern. It is widely disparaged as abominable and culturally subversive music. However, vulgar lingo has always been a functional and ornamental component of speech and song in specific contexts of the Shona cultural community. Deploying the aesthetics of vulgarity thesis, this article appreciates the place of raw Zimdancehall in today’s society and its representation of the socio-political realities of life. The genre represents a discursive space for artists to expose, interrogate and demystify the hidden dimensions of individuals and societal experiences, perceptions, fallacies, fantasies and aspirations that are often overlooked and avoided by mainstream musicians through the use of nonconformist discourse. This illustrates the reincarnation of traditional art and spaces where vulgar served to create humour, expose, contest and critique existing socio-political veracities in the society. We contend that the criminalization of vulgarised Zimdancehall is a culturally uninformed legally supported verdict that disregards the traditional functions and place of vulgarised performances. The misconduct is not in the composition and production of the music, but in individuals who play the music in wrong contexts without discerning the content.